Soil Carbon and Nutrient Dynamics Following Cessation of Anthropogenic Disturbances in Degraded Subtropical Forests. (25th September 2017) - Feng, Chun; Ma, Yan; Fu, Songling; Chen, Han Y.H.
Abstract: Soil carbon (C) and nutrient availability is fundamental to terrestrial biodiversity and functionality. In recent decades, the restoration of degraded forests has become a major concern worldwide, and recent studies have demonstrated that soil C and nitrogen (N) increase over time following restoration. However, our understanding of the responses of soil phosphorus (P), calcium (Ca), potassium (K) and magnesium (Mg) and elemental stoichiometric ratios to restoration remains elusive. We employed a chronosequence to examine the responses of C and macronutrients in three soil layers (0–10 cm, 10–20 cm and 20–30 cm) to the time (0 to 31 years) since the cessation of anthropogenic disturbances in the degraded subtropical forests of Eastern China. We found that stand basal area, soil water content, organic matter content and C concentration and stock increased, while soil pH and bulk density decreased over time, with the most pronounced effects within the 0–10 cm layer. Total and available N and K as well as available P and total Mg increased, while total P in the 20–30 cm layer and Ca in all soil layers decreased over time. The mass concentration ratios of soil C to total N and available N, P and K decreased, whereas those for C to total P and Ca as well as total N to total P and available N to available P increased over time. Our results suggest that soil C accumulation and biologically driven nutrients increase, while nutrients that are driven primarily through geochemical mechanisms decrease with live biomass accumulation following restoration. Copyright © 2017 John Wiley & Sons, Ltd.